Respuesta :
y = 3x - 7
6x - 2y = 12
6x - 2(3x-7) = 12
6x - 6x -7 = 12
-7 = 12
6x - 2y = 12
6x = 12 + 2y
x = 12/6 + 2y/6
x = 2 + y/3
y = 3x - 7
y = 3(2 + y/3) - 7
y = 6 + 3y/3 - 7
y = 6 + y - 7
y - y = 6-7
0 = -1
B.) THERE IS NO SOLUTION.
6x - 2y = 12
6x - 2(3x-7) = 12
6x - 6x -7 = 12
-7 = 12
6x - 2y = 12
6x = 12 + 2y
x = 12/6 + 2y/6
x = 2 + y/3
y = 3x - 7
y = 3(2 + y/3) - 7
y = 6 + 3y/3 - 7
y = 6 + y - 7
y - y = 6-7
0 = -1
B.) THERE IS NO SOLUTION.
subsitution
ok so
y=3x-7
subsitute 3x-7 for y since they are equal
6x-2(3x-7)=12
distribute
6x-6x-7=12
add like terms
0x-7=12
-7=12
false
therefor there is no solution
B is teh answer
ok so
y=3x-7
subsitute 3x-7 for y since they are equal
6x-2(3x-7)=12
distribute
6x-6x-7=12
add like terms
0x-7=12
-7=12
false
therefor there is no solution
B is teh answer